Preparation and Flame Retardancy of Poly(ethylene terephthalate)/Montmorillonite Nanocomposites - HABIBI, S.; RASHIDI, A.; BAZGIR, S.; KATBAB, A.A.; MONTAZER, M. (Asian Journal of Chemistry, 2010)
This paper presents the experiments on preparing nanocomposites based on poly(ethylene terephthalate) (PET) and montmorillonite via melt blending with different clay loadings to investigate their combustion behaviour. All the samples have intercalated structure by X-ray diffraction (XRD) and transmission electron microscopy. Their thermal stability and combustion behaviour were investigated by using thermogravimetric analysis (TGA), limiting oxygen index (LOI) and cone calorimeter. Peak heat release rate of nanocomposites decrease as the contents of clay increase compared to that of pristine poly(ethylene terephthalate).